Monoacylglycerol Lipase Knockdown Inhibits Cell Proliferation and Metastasis in Lung Adenocarcinoma - Zhang, Hao; Guo, Wei; Zhang, Fan; Li, Renda; Zhou, Yang; Shao, Fei; Feng, Xiaoli; Tan, Fengwei; Wang, Jie; Gao, Shugeng; Gao, Yibo; He, Jie (Frontiers in Oncology, 2020)
Abnormal metabolism is one of the hallmarks of cancer cells. Monoacylglycerol lipase (MGLL), a key enzyme in lipid metabolism, has emerged as an important regulator of tumor progression. In this study, we aimed to characterize the role of MGLL in the development of lung adenocarcinoma (LUAD). To this end, we used tissue microarrays to evaluate the expression of MGLL in LUAD tissue and assessed whether the levels of this protein are correlated with clinicopathological characteristics of LUAD. We found that the expression of MGLL is higher in LUAD samples than that in adjacent non-tumor tissues. In addition, elevated MGLL expression was found to be associated with advanced tumor progression and poor prognosis in LUAD patients. Functional studies further demonstrated that stable short hairpin RNA (shRNA)-mediated knockdown of MGLL inhibits tumor proliferation and metastasis, both in vitro and in vivo, and mechanistically, our data indicate that MGLL regulates Cyclin D1 and Cyclin B1 in LUAD cells. Moreover, we found that knockdown of MGLL suppresses the expression of matrix metalloproteinase 14 (MMP14) in A549 and H322 cells, and in clinical samples, expression of MMP14 is significantly correlated with MGLL expression. Taken together, our results indicate that MGLL plays an oncogenic role in LUAD progression and metastasis and may serve as a potential biomarker for disease prognosis and as a target for the development of personalized therapies.